Stages and main tasks of the century-long the control theory and system identification development. Part I. State space method in the theory of linear automatic control systems - Romanenko, V.; Gubarev, V. (Проблеми керування та інформатики, 2023)
This article initiates a series of publications dedicated to the scientific and technical achievements of the century-long development of control theory and methods. It outlines problems that have been fully addressed through various approaches. The first article in this series focuses on the state-space method, which began to gain traction in the 1970s–1980s within systems theory and general systems theory. Ця стаття відкриває серію публікацій, присвячених науково-технічним досягненням сторічного періоду розвитку теорії та методів керування. Описано проблеми, які вдалося повністю вирішити з урахуванням того чи іншого підходу. Перша з цих статей присвячена методу простору станів, який почав активно розвиватися десь із 70–80-х років минулого століття у рамках теорії систем та загальної теорії систем.